Estimation of shipping emissions based on real-time data with different methods: A case study of an oceangoing container ship - Ekmekcioglu, Araks; Unlugencoglu, Kaan; Celebi, Ugur Bugra (SPRINGER, 2022)
The environmental consequences of ship-based greenhouse emissions have been increasingly significant as a result of the rise in the share of maritime transportation in international trade. Transnational organizations such as the European Union and the International Maritime Organization monitor these emissions and have come to limit some gas emissions such as SOx, NOx, PM, and CO2. These limiting measures are all needed and welcome. However, we need more accurate data to inform and implement even more concrete policies. This study contributes to such efforts by providing calculations of the emissions of NOx, NMVOC, PM, SOx, CO, and CO2 from an oceangoing container ship during its 37-day voyage in 2019. The use of a real case scenario differentiates this study from others. We employed two conventionally used methods to make the estimations. One is the fuel-based approach (top-down) and the other is the activity-based approach (bottom-up). While there is some discrepancy of results produced by the two methods, there is also consistency in terms of percentages regarding which gas is emitted most and when. The results indicate that by taking appropriate measures such as reducing fuel consumption, and using low-sulfur fuel, as well as optimizing port traffic, the environmental damage of maritime transportation could be reduced.
Keywords: Global warming; Port emissions; Green shipping; Container ship emissions; ENERGY-CONSUMPTION; EXHAUST EMISSIONS; INVENTORY; FUEL; GAS; CHINA; MODEL; PORT; Science & Technology - Other Topics; Environmental Sciences & Ecology